Cardiac changes after cardiac resynchronization therapy assessed using cardiac magnetic resonance imaging during biventricular pacing. (25th November 2020) - Czimbalmos, C; Papp, R; Szabo, L; Toth, A; Csecs, I; Suhai, F.I; Molnar, L; Kosztin, A; Geller, L; Merkely, B; Vago, H
Abstract: : Cardiac magnetic resonance (CMR) is a valuable tool in the assessment of left and right ventricular volumes and functions therefore establishing the effect of cardiac resynchronization therapy (CRT), but in majority of the devices MR safe mode does not include biventricular pacing as an option. We aimed to assess the effect of cardiac resynchronization using CMR with resynchronization on. NYHA class II-III patients with LVEF≤35% despite optimal medical therapy and complete LBBB with broad QRS (>150 ms) were prospectively recruited (n=16, 65±7 years, 56% male, 69% nonischaemic). CMR examination was performed at baseline and at 6-month follow-up, applying both biventricular and AOO pacing. The following data were measured: conventional CMR parameters including left and right ventricular ejection fraction (LVEF), end-diastolic index (LVEDVi) and end-systolic volume index (LVESVi), stroke volume and mass, remodelling indices such as 3D sphericity and relative wall thickness (RWT: 2x end-diastolic wall thickness /end-diastolic long-axis diameter). Using feature tracking analysis global longitudinal, circumferential, radial strain, global dyssynchrony (mechanical dispersion (MD)) and regional dyssynchrony was measured. Comparing the baseline and follow-up CMR parameters measured during biventricular pacing, we found a significant increase in LVEF (27±7 vs 45±9%; p<0.001) and decrease in LVEDVi and LVESVi (LVEDVi: 149±28 vs 91±20ml/m 2 ; LVESVi: 108±31 vs 51±17ml/m 2 ; p<0.001). Based on decrease in LVESVi 14 patients were classified as super-responder (>30%), one responder (>15%) and one non-responder (<15%). ProBNP levels significantly decreased (1186±83 vs 323±271 pg/ml, p<0.05). LV remodelling indices (3D sphericity: 0.46±0.13 vs 0.61±0.11, RWT: 0.33±0.07 vs 0.43±0.10), global longitudinal, circumferential and radial strain values showed significant improvement. Circumferential MD decreased (18.3±6.7 vs 13.3±3.4, p<0.01), while longitudinal MD did not change. Regional dyssynchrony drastically improved (358±108 vs 98±61ms, p<0.001). Applying AOO pacing resulted in an immediate deterioration in LVEF (45±9 vs 38±9%), LVESVi (51±17 vs 58±19 ml/m 2 ), global circumferential and radial strain and regional dyssynchrony. In conclusion CMR imaging during biventricular pacing is feasible and enables a more precise quantification of LV function, morphology and mechanics. As a result, it may contribute to a better understanding of the effects of resynchronization therapy and might improve responder rate in the future. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary (NKFIA)